The birth of the pill : how four crusaders reinvented sex and launched a revolution - Eig, Jonathan (W. W. Norton & Company, 2014)
Immersed in radical feminist politics, scientific ingenuity, establishment opposition, and, ultimately, a sea change in social attitudes, this is the fascinating story of one of the most important scientific discoveries of the twentieth century.